Ubiquitous Convergence Technology First International Conference, ICUCT 2006, Jeju Island, Korea, December 5-6, 2006, Revised Selected Papers - Stajano, Frank; Kim, Hyoung Joong; Chae, Jong-Suk.; Kim, Seong-Dong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Ubiquitous computing is already with us and is changing our lifestyle, way of thinking and quality of life. Everyday objects with embedded computing - pabilities are now commonplace and, between mobile phones and RFID tags, further deployment proceeds at an unstoppable pace. The next major step of the ubiquitous computing evolution is the move, already partly underway, from isolated smart objects to distributed systems of smart objects and appropriate back-end infrastructure: microelectronics and communication technology c- verging with healthcare technology, communication technology, sports and - tertainment, housing, vehicular technology, middleware, sensor networks and so on. You will have noticed that many people in the ?eld now use the word (3z(Bub- uitous(3y (Bnot to mean (3z(Bpresent everywhere(3y (Bbut as a shorthand for (3z(Bubiquitous computing and communications(3y$1 (Bleading to otherwise inexplicable locutions such as (3z(Bthe ubiquitous society(3y(B. Rather than continuing to ?ght this syn- dochical use we have chosen to go with the ?ow, in so far as the change in language is an indication of the global spread of the meme. We have therefore chosen (3z(Bubiquitous convergence(3y (Bas a concise description of the above view: a systems-oriented perspective encompassing both the technology and its appli- tions.s
Keynotes -- Video Coding Techniques for Ubiquitous Multimedia Services -- Multimedia -- Residual Signal Compression Based on the Blind Signal Decomposition for Video Coding -- Personalized Life Log Media System in Ubiquitous Environment -- An Embedded Variable Bit-Rate Audio Coder for Ubiquitous Speech Communications -- Performance Enhancement of Error Resilient Entropy Coding Using Bitstream of Block Based SPIHT -- A Study on the Personal Program Guide Technique Within Ubiquitous Media Community Environment Using Multi-band Sensor Gateway -- Applications -- Remote Diagnostic Protocol and System for U-Car -- Map-Building and Localization by Three-Dimensional Local Features for Ubiquitous Service Robot -- LRMAP: Lightweight and Resynchronous Mutual Authentication Protocol for RFID System -- Novel Process Methodology of Smart Combi Card (SCC) Manufacturing for RFID/USN -- Product Control System Using RFID Tag Information and Data Mining -- iSCSI Protocol Parameter Optimization for Mobile Appliance Remote Storage System at Smart Home Environment Approach -- Mobile, Wireless, and Ad Hoc Networking -- A Study on Optimal Fast Handover Scheme in Fast Handover for Mobile IPv6 (FMIPv6) Networks -- DCAR: Dynamic Congestion Aware Routing Protocol in Mobile Ad Hoc Networks -- Anonymous Secure Communication in Wireless Mobile Ad-Hoc Networks -- A DiffServ Management Scheme Considering the Buffer Traffic Rate in Ubiquitous Convergence Network -- An Approach to Reliable and Efficient Routing Scheme for TCP Performance Enhancement in Mobile IPv6 Networks -- Ant Colony Optimization for Satellite Customer Assignment -- Advanced Remote-Subscription Scheme Supporting Cost Effective Multicast Routing for Broadband Ubiquitous Convergence IP-Based Network -- Smart Sensors and Sensor Networks -- Dual Priority Scheduling Based on Power Adjust Context Switching for Wireless Sensor Network -- WODEM: Wormhole Attack Defense Mechanism in Wireless Sensor Networks -- Layer-Based ID Assigning Method for Sensor Networks -- A Smart Sensor Overlay Network for Ubiquitous Computing -- An Efficient Sensor Network Architecture Using Open Platform in Vehicle Environment -- Privacy and Security -- Improved Reinforcement Computing to Implement AntNet-Based Routing Using General NPs for Ubiquitous Environments -- Web-Based Simulation, Natural System -- Design of a Cooperative Distributed Intrusion Detection System for AODV -- Towards a Security Policy for Ubiquitous Healthcare Systems (Position Paper) -- Architecture of an LBS Platform to Support Privacy Control for Tracking Moving Objects in a Ubiquitous Environments -- A New Low-Power and High Speed Viterbi Decoder Architecture -- Dynamic EPG Implementation for Ubiquitous Environment.
Keywords: Computer science; Computer communication systems; Special purpose computers; Computers; Multimedia information systems; User interfaces (Computer systems).; Computer Science; Theory of Computation; Computer Communication Networks; Special Purpose and Application-Based Systems; Information Systems Applications (incl. Internet).; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Electronic books